Analysis of Corporate Investment Behaviour in Digital Technologies for Organisational Development Purposes - Olena Skrynnyk (Financial Markets, Institutions and Risks)
In the context of this study, a literature review and the survey of German business executives were conducted. On the way to digitalisation, companies try to support or replace as many processes as possible using software and tools. The main purpose of this study consisted in investigating corporate investment behaviour in digital technologies for organisational development. Since the progress in this area in recent period is very large, consists the need to determine how do companies choose the appropriate functions and how much are they willing to invest for their execution. The study relies on a review of recent publications, statistical analysis and empirical analysis based on the results of online surveys. Behavioural determinants defined include regularity and predictability of organisational development, spending points, purpose of investment, previous experience with investment object, possible reasons against investment. It was compared which characteristics of companies (number of employees, annual turnover, age of the company, orientation) can influence a statement about the level of investment in organisational development, as well as desired functions and possible decision against investment in digital technologies. Furthermore, the current expenditures for organisational development were compared with the investments of companies with the same characteristics. The results demonstrate the different distribution of statistically collected data for personal purposes and the estimated investment volumes for digital tools for organisational development, despite relatively similar figures for current expenditure on organisational development.